تواصلية الفن الإسلامي النظرية والتطبيق - إدهام محمد حنش (International Institute of Islamic Thought, 2013)
يحاول هذا البحث استكشاف معالم نظرية إسلامية لثقافة التواصل الإنسانية عبر الفن، بوصفه لغة من اللغات الكونية المشتركة بين الشعوب والحضارات، وعبر الصورة بوصفها الوسيلة والرسالة معاً، التي يقوم عليها علم التواصل الخاص بالفن الإسلامي. إنّ ثقافة التواصل الإنسانية هي نظرية كونية عامة في المعرفة الإنسانية، وتدخل في كل مجالات هذه المعرفة بلا استثناء، ولكنها تعمل عبر مجال المعرفة الفنية أكثر من المجالات الأخرى، حتى صار التصميم التواصلي هو القاعدة المعرفية العريضة لكل تقنيات التواصل الفنية: التصويرية، والخطية، والطباعية في صناعة الكتاب والإعلان المرئي وغيرهما. لكن المؤسف أن نظرية التواصل الشائعة اليوم هي نظرية غربية بامتياز؛ من حيث التصنيف المعرفي، وتكاد تختص بحقل الإعلام أو الاتصال. وقد استبعدت هذه النظرية أية عناصر إسلامية في تكوين التواصل الإنساني. This study tries to explore the parameters of an Islamic theory of the culture of human communication through Art which is a universal language common among peoples and civilizations, and also through the Image as it is both the Medium and the Message. The image is a special communication science of Islamic art; called Communicatology of Islamic Art. The theory of human communication today is a universal theory that has a place in almost all disciplines of knowledge, especially in the art. The communication design has become the broad epistemological base for all techniques of art communication, i. e. photography, calligraphy, industry of book printing, and visual advertizing, etc. However it sad to see the prevailing communication theory as a Western theory par excellence in terms of knowledge classification, and has ruled out any Islamic elements that may be essential components of human communication.